Human Resource Development Programs and Their Contribution to Employee Career Advancement in State Universities - Kurniasi, Intan; Akbar, Iham (Generasi Sains Indonesia, 2025)
This study examines the contribution of Human Resource Development (HRD) programs to employee career advancement in state universities, emphasizing how training, mentoring, leadership development, digital literacy initiatives, and research support shape professional growth within higher education institutions. Using a quantitative correlational design, data were collected from 220 academic, administrative, and support staff selected through proportional stratified random sampling. Structured questionnaires measured HRD participation and career advancement indicators, followed by descriptive analysis, Pearson correlation, and regression testing. The findings reveal that HRD programs significantly enhance employees’ competencies, motivation, and job satisfaction, while also demonstrating a strong positive relationship with career advancement outcomes. Despite these benefits, the study indicates that developmental participation does not always translate into equitable promotional opportunities due to institutional structures and limited leadership pathways. HRD contributes 45.3 percent of the variance in career advancement, confirming its strategic importance yet highlighting the need for stronger alignment between development initiatives and promotion systems. The study concludes that universities must elevate HRD as a core element of human capital governance and strengthen its link to transparent career progression. Future research should adopt longitudinal or mixed-method approaches to further explore institutional factors shaping advancement.